Method for preparing sulfur-rich polymer by multi-component anionic hybrid copolymerization
By adding a third monomer to the copolymerization system of elemental sulfur and binary olefins, using anion hybrid copolymerization method, a sulfur-rich polymer was synthesized in one-step under mild reaction conditions, which solved the high-temperature reaction and limited monomer types in the existing methods. The problem of this paper has achieved efficient and low-cost sulfur-rich polymer synthesis, improving the performance and application potential of the material.
Patent Information
- Application Number
- CN202310257132.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-03-16
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2043-03-16
AI Technical Summary
The existing sulfur-rich polymer synthesis methods have problems such as high temperature reactions, limited monomer types, and safety hazards, which are difficult to meet the needs of large-scale industrial production and functional applications.
The sulfur-rich polymer was synthesized in one-step under mild reaction conditions by adding a third monomer to the copolymerization system of elemental sulfur and binary olefins.
The synthesis of sulfur-rich polymers under mild reaction conditions is achieved, reducing production costs and time, expanding the selection range of monomers, and improving the mechanical properties and degradability of the materials.
Smart Images

Figure HDA0004190538870000011 
Figure HDA0004190538870000012 
Figure HDA0004190538870000013
Abstract
Description
Technical Field
[0001] The invention belongs to the field of polymer synthesis, and in particular relates to a method for preparing a sulfur-rich polymer by multi-component anionic hybrid copolymerization. Background Art
[0002] Sulfur is one of the most abundant elements on earth. Every year, a large amount of elemental sulfur is discovered with the exploitation of oil. Only a small part of this elemental sulfur is used to prepare sulfuric acid or vulcanize rubber, and the vast majority is idle, causing huge waste. Moreover, due to its flammable properties, idle sulfur is very likely to cause fires, posing a huge safety hazard.
[0003] Directly using elemental sulfur as a raw material to prepare sulfur-rich polymers not only makes use of idle sulfur, but also solves the problem of "excess sulfur". Moreover, compared with introducing sulfur into polymers through other functional groups with high production costs such as thiol, disulfide, thioester and thioamide, using elemental sulfur as a sulfur source greatly reduces the production cost. At present, there are several methods for directly using elemental sulfur as a raw material to prepare sulfur-containing polymers, such as: copolymerization of dibasic acid, diisocyanate and elemental sulfur to generate thioamide, ring-opening polymerization of cyclic sulfide compounds and elemental sulfur anions to generate polysulfide, and reverse vulcanization reaction through high-temperature cracking free radical polymerization of elemental sulfur.
[0004] Although existing methods can directly introduce sulfur into polymers, these methods all have defects to a certain extent. For example, binary isonitrile and episulfide monomers are relatively expensive and have limited monomer types, making them unsuitable for large-scale industrial production; and traditional inverse vulcanization methods must be carried out at higher temperatures, which are not suitable for some low-boiling monomers, and react at this temperature, accompanied by H 2 The release of sulfur gas poses a safety hazard. At the same time, the types of monomers covered by existing synthesis methods are limited, which directly affects the synthesis of sulfur-rich polymers and the development of functional applications. Therefore, lowering the polymerization reaction temperature, expanding the polymerizable monomers, and developing new synthetic pathways for polysulfides have become the focus and difficulty of the sulfur-rich material preparation industry. Summary of the invention
[0005] In order to solve the defects of the existing sulfur-containing polymer synthesis route, the present invention proposes to synthesize sulfur-rich polymers in one step by adding other third monomers to the copolymerization system of catalytic elemental sulfur and diolefins through anionic hybrid copolymerization under relatively mild reaction conditions. The synthesis method of the sulfur-rich compound of the present invention has the characteristics of mild reaction conditions, wide monomer selection, and one-step synthesis.
[0006] In order to achieve the above objectives, the present invention is implemented by the following technical solutions:
[0007] A method for preparing a sulfur-rich polymer by multi-component anionic hybrid copolymerization: an olefin monomer, elemental sulfur, and a third monomer are combined into a ternary copolymerization system in the presence of a small amount of catalyst under a mild heating environment to synthesize the sulfur-rich polymer in one step.
[0008] Furthermore, the reaction environment is a dry environment protected by inert gas, the reaction temperature is 0-70° C., and the reaction time is 6-24 h.
[0009] The feed weight ratio of the synthesized sulfur-rich polymer monomer of the present invention is 20-40wt% of olefin monomer, 20-40wt% of elemental sulfur, 20-50wt% of the third monomer and 0.1-0.8wt% of the catalyst.
[0010] The vinyl monomers are styrene (St), divinylbenzene (DIB), ethyl acrylate (EA), methyl methacrylate (MMA), and trimethylolpropane triacrylate (TMPTA).
[0011] The third monomer is one or more of caprolactone (CL), valerolactone (VL), caprolactam (CPL), trimethylene carbonate (DO), hexamethylene diisocyanate (HDI), bisphenol A diisocyanate (BCPP), and ethylene sulfide (ES).
[0012] The catalyst is 4-dimethylaminopyridine (DMAP), tris(3,4,5-trimethoxyphenyl)phosphine (TMPP) or phosphazene base (t-BuP 2 ).
[0013] The sulfur-rich polymer of the invention is used in the fields of energy storage materials and degradable materials.
[0014] Beneficial effects:
[0015] The raw material elemental sulfur S in the present invention 8 It is a natural product, environmentally friendly, harmless and inexpensive.
[0016] The method for preparing sulfur-rich polymers by multi-component anionic hybrid copolymerization provided by the present invention is a one-step synthesis, which greatly reduces the time and economic cost of polysulfide polymer synthesis.
[0017] The method for preparing sulfur-rich polymer by multi-component anionic hybrid copolymerization provided by the present invention has a wide range of selectable monomers, and acrylate monomers, cyclic lactones, cyclic lactams, cyclic carbonates, cyclic sulfides, isocyanates, etc. can all be used as reaction monomers.
[0018] The method for preparing sulfur-rich polymer by multi-component anionic hybrid copolymerization provided by the present invention has relatively mild polymerization reaction conditions and can be polymerized under reaction conditions below 70°C.
[0019] The method for preparing sulfur-rich polymers by multi-component anionic hybrid copolymerization provided by the present invention has a large number of SS bonds in the product that dynamically interact, giving the material "glass-like" properties, and the material has excellent mechanical properties, repeatable processing properties and degradation properties after molding. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 FTIR spectra of the product Poly(S-TMPTA-CL) and elemental sulfur in Example 3.
[0021] Figure 2 The tensile stress-strain curves of the products Poly(S-TMPTA-CL) and Poly(S-TMPTA) in Example 3.
[0022] Figure 3 The XRD spectra of the product Poly(S-TMPTA-CL) and elemental sulfur in Example 3 are shown.
[0023] Figure 4 These are the degradation test results of the products of Example 4, Poly(S-TMPTA-CL) and Poly(S-TMPTA)) in an aqueous solution at pH=1.
[0024] Figure 5 The tensile stress-strain curves of the products of Example 4, Poly(S-TMPTA-CL) and Poly(S-TMPTA).
[0025] Figure 6 The degradation test results of the products of Example 3, Poly(S-TMPTA-CL) and Poly(S-TMPTA), in an aqueous solution at pH=1 are shown.
[0026] Figure 7 FTIR spectra of the product Poly(S-TMPTA-HDI) and monomer HDI in Example 5.
[0027] Figure 8 The XRD spectra of the product Poly(S-TMPTA-HDI) and elemental sulfur in Example 5 are shown in FIG.
[0028] Fig. 9 FTIR spectra of the product Poly(S-TMPTA-ES) and ES monomer in Example 7.
[0029] Fig.10 FTIR spectra of the product Poly(S-TMPTA-BCPP) and elemental sulfur in Example 9.
[0030] Fig.11The tensile stress-strain curves of the products of Example 9, Poly(S-TMPTA-BCPP) and Poly(S-TMPTA).
[0031] Fig.12 The degradation test results of the products Poly(S-TMPTA-BCPP) and Poly(S-TMPTA) in Example 9 in an aqueous solution at pH=1 are shown.
[0032] Fig.13 The impact performance test results of the product Poly (S-TMPTA-BCPP) in Example 9 are shown in FIG.
[0033] Fig.14 The tensile stress-strain curves of the products Poly(S-TMPTA-CO) and Poly(S-TMPTA) in Example 11.
[0034] Fig.15 This is the tensile stress-strain curve of the product Poly(S-TMPTA-DLLA) in Comparative Example 5. DETAILED DESCRIPTION
[0035] The technical solutions in the embodiments of the present invention will be described clearly and completely below in combination with the embodiments of the present invention and the accompanying drawings. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0036] Example 1
[0037] Weigh 0.512g of elemental sulfur powder, 0.398g of styrene (St), 0.114g of caprolactone (CL) and 200μL of DMAP (2.02mg) into a 10mL flask, and stir and react at room temperature under inert gas protection for 6h. After the reaction, the mixture is repeatedly precipitated and washed with a precipitant, and dried in a vacuum oven to give a yield of 97.3wt%.
[0038] Example 2
[0039] Weigh 0.512 g of elemental sulfur powder, 0.473 g of divinylbenzene (DIB), 0.114 g of caprolactone (CL), and 5 μL of t-BuP 2 In a 10 mL flask, under the protection of inert gas, the mixture was stirred and reacted at 40° C. for 3 h. After the reaction was completed, the mixture was repeatedly precipitated and washed with a precipitant. After drying in a vacuum oven, the yield reached 98.7 wt%.
[0040] Example 3
[0041] Weigh 0.512 g of elemental sulfur powder, 0.428 g of trimethylolpropane triacrylate (TMPTA), 0.389 g of caprolactone (CL), and 5 μL of t-BuP 2 In a 10 mL flask, under the protection of inert gas, the mixture was mixed and reacted at 50° C. for 3 h. After the reaction was completed, the mixture was repeatedly precipitated and washed with a precipitant, and dried in a vacuum oven. The yield reached 92.4 wt%.
[0042] Comparative Example 1
[0043] Weigh 0.512 g of elemental sulfur powder, 0.548 g of trimethylolpropane triacrylate (TMPTA) and 5 μL of t-BuP 2 In a 10 mL flask, under the protection of inert gas, the mixture was mixed and reacted at 50° C. for 3 h. After the reaction was completed, the mixture was repeatedly precipitated and washed with a precipitant, and dried in a vacuum oven. The yield reached 88.3 wt%.
[0044] Example 4
[0045] Weigh 0.512 g of elemental sulfur powder, 0.428 g of trimethylolpropane triacrylate (TMPTA), 0.246 g of caprolactone (CL), and 5 μL of t-BuP 2 In a 10 mL flask, under the protection of inert gas, the mixture was mixed and reacted at 50° C. for 3 h. After the reaction was completed, the mixture was repeatedly precipitated and washed with a precipitant, and dried in a vacuum oven. The yield reached 94.6 wt%.
[0046] Comparative Example 2
[0047] Weigh 0.512 g of elemental sulfur powder, 0.638 g of trimethylolpropane triacrylate (TMPTA) and 5 μL of t-BuP 2 In a 10 mL flask, under the protection of inert gas, the mixture was stirred and reacted at 40° C. for 3 h. After the reaction was completed, the mixture was repeatedly precipitated and washed with a precipitant, and dried in a vacuum oven to give a yield of 99.7 wt%.
[0048] Example 5
[0049] Weigh 0.256g of elemental sulfur powder, 0.398g of trimethylolpropane triacrylate (TMPTA), 0.187g of hexamethylene diisocyanate (HDI) and 10μL of DMAP in a 10mL flask, and stir and react at room temperature for 12h under the protection of inert gas. After the reaction, the mixture is repeatedly precipitated and washed with a precipitant, and the yield reaches 99.6wt% after drying in a vacuum oven.
[0050] Example 6
[0051] Weigh 0.256 g of elemental sulfur powder, 0.228 g of ethyl acrylate (EA), 0.136 g of hexamethylene diisocyanate (HDI), and 10 μL of t-BuP 2 In a 10 mL flask, under the protection of inert gas, the mixture was stirred and reacted at room temperature for 24 h. After the reaction was completed, the mixture was repeatedly precipitated and washed with a precipitant, and dried in a vacuum oven. The yield reached 97.6 wt%.
[0052] Example 7
[0053] 0.512 g of elemental sulfur powder, 0.12 g of trimethylolpropane triacrylate (TMPTA), 0.114 g of ethylene sulfide (ES) and 3 mg of TMPP were weighed into a 10 mL flask, and stirred under inert gas protection at room temperature for 6 h. After the reaction, the mixture was repeatedly precipitated and washed with a precipitant, and dried in a vacuum oven to give a yield of 97.3 wt%.
[0054] Example 8
[0055] Weigh 0.512 g of elemental sulfur powder, 0.417 g of methyl methacrylate (MMA), 0.246 g of bisphenol A diisocyanate (BCPP) and 5 μL of t-BuP 2 In a 10 mL flask, under the protection of inert gas, the mixture was mixed and reacted at room temperature for 3 h. After the reaction was completed, the mixture was repeatedly precipitated and washed with a precipitant, and dried in a vacuum oven. The yield reached 93.6 wt%.
[0056] Example 9
[0057] Weigh 0.512g of elemental sulfur powder, 0.398g of trimethylolpropane triacrylate (TMPTA), 0.114g of bisphenol A diisocyanate (BCPP) and 200μL of DMAP in a 10mL flask, and stir and react at room temperature for 12h under the protection of inert gas. After the reaction, the mixture is repeatedly precipitated and washed with a precipitant, and the yield reaches 99.6wt% after drying in a vacuum oven.
[0058] Performance test: tensile performance test and impact performance test are carried out at 25℃.
[0059] Comparative Example 3
[0060] Weigh 0.512 g of elemental sulfur powder, 0.428 g of trimethylolpropane triacrylate (TMPTA) and 200 μL DMAP into a 10 mL flask, and stir and react at room temperature for 12 h under inert gas protection. After the reaction, the mixture is repeatedly precipitated and washed with a precipitant, and dried in a vacuum oven to give a yield of 98.8 wt%.
[0061] Example 10
[0062] Weigh 0.256 g of elemental sulfur powder, 0.238 g of trimethylolpropane triacrylate (TMPTA), 0.326 g of caprolactone (CL), and 10 μL of t-BuP 2 In a 10 mL flask, under the protection of inert gas, the mixture was mixed and reacted at room temperature for 12 h. After the reaction, the mixture was repeatedly precipitated and washed with a precipitant, and dried in a vacuum oven. The yield reached 92.5 wt%.
[0063] Embodiment 11
[0064] Weigh 0.256g of elemental sulfur powder, 0.5g of trimethylolpropane triacrylate (TMPTA), 0.126g of trimethylene carbonate (DO) and 300μL of DMAP in a 10mL flask, and react at 40°C for 6h under inert gas protection. After the reaction, the mixture is repeatedly precipitated and washed with a precipitant, and dried in a vacuum oven to give a yield of 91.6wt%.
[0065] Comparative Example 4
[0066] Weigh 0.256g of elemental sulfur powder, 0.428g of trimethylolpropane triacrylate (TMPTA), and 300μL DMAP into a 10mL flask, and react at 40°C for 6h under inert gas protection. After the reaction, the mixture is repeatedly precipitated and washed with a precipitant, and dried in a vacuum oven to give a yield of 93.6wt%.
[0067] Example 12
[0068] 0.256 g of elemental sulfur powder, 0.485 g of trimethylolpropane triacrylate (TMPTA), 0.264 g of caprolactam (CPL) and 5 mg of TMPP were weighed into a 10 mL flask, mixed and reacted at 70 ° C for 6 h under inert gas protection. After the reaction, the mixture was repeatedly precipitated and washed with a precipitant, and dried in a vacuum oven to give a yield of 94.5 wt%.
[0069] Comparative Example 5
[0070] 0.256 g of elemental sulfur powder, 0.485 g of trimethylolpropane triacrylate (TMPTA), 0.264 g of lactide (DLLA) and 5 mg of TMPP were weighed into a 10 mL flask, and mixed and reacted at 70° C. for 6 h under the protection of inert gas. After the reaction, the mixture was repeatedly precipitated and washed with a precipitant, and dried in a vacuum oven. The yield reached 84.5 wt %. Fig.15 .
[0071] Embodiment 13
[0072] Weigh 0.256 g of elemental sulfur powder, 0.408 g of ethyl acrylate (EA), 0.101 g of valerolactone (VL) and 4 mg of TMPP into a 10 mL flask, and stir and react at 70 ° C for 3 h under inert gas protection. After the reaction is completed, the mixture is repeatedly precipitated and washed with a precipitant, and the yield reaches 99.2 wt% after drying in a vacuum oven.
[0073] Embodiment 14
[0074] 0.256 g of elemental sulfur powder, 0.485 g of trimethylolpropane triacrylate (TMPTA), 0.264 g of valerolactone (VL) and 5 mg of TMPP were weighed into a 10 mL flask, mixed and reacted at 70 ° C for 6 h under inert gas protection. After the reaction, the mixture was repeatedly precipitated and washed with a precipitant, and dried in a vacuum oven to give a yield of 94.5 wt%.
[0075] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.
Claims
1. A sulfur-rich polymer, characterized in that The sulfur-rich polymer is composed of 20-40 wt% of olefin monomer, 20-40 wt% of elemental sulfur, 20-50 wt% of the third monomer, and 0.1-0.8 wt% of the catalyst in terms of mass percentage; The vinyl monomers are: styrene, divinyl benzene, ethyl acrylate, methyl methacrylate, trimethylolpropane triacrylate; The third monomer is one or more of caprolactone, valerolactone, caprolactam, trimethylene carbonate, hexamethylene diisocyanate, bisphenol A diisocyanate, and ethylene sulfide.
2. The sulfur-rich polymer according to claim 1, characterized in that The catalyst is 4-dimethylaminopyridine, tris(3,4,5-trimethoxyphenyl)phosphine or phosphazene base.
3. A method for preparing a sulfur-rich polymer according to claim 1, characterized in that: The sulfur-rich polymer is prepared by multi-component anionic hybrid copolymerization, specifically: an olefin monomer, elemental sulfur, and a third monomer are combined into a ternary copolymerization system in the presence of a catalyst under a mild environment, and the sulfur-rich polymer is synthesized by a one-step hybrid copolymerization reaction.
4. The method for preparing a sulfur-rich polymer according to claim 3, characterized in that: The hybrid copolymerization reaction environment is a dry environment protected by inert gas.
5. The method for preparing a sulfur-rich polymer according to claim 3, characterized in that: The hybrid copolymerization reaction temperature is 0-70° C., and the copolymerization reaction time is 6-24 h.
6. An application of the sulfur-rich polymer according to claim 1, characterized in that: The sulfur-rich polymer is used in the fields of energy storage materials and degradable materials.
Citation Information
Patent Citations
Sulfur-based functional prepolymers for polyurethanes and polymeric materials
WO2021158730A1